GoodFellas [videorecording (DVD)] - Winkler, Irwin; Scorsese, Martin; De Niro, Robert; Liotta, Ray; Pesci, Joe; Pileggi, Nicholas (Warner Home Video, 1999)
Henry Hill had always wanted to be a gangster, until three decades later when his life comes crashing down around him.